Threshold analysis of indicator traits for involuntary disposal in Holstein Friesian crossbred cattle - DASH, SHAKTI KANT; GUPTA, ASHOK KUMAR; SINGH, AVTAR; CHAKRAVARTY, A K; MANOJ, M; KUMAR, VIRENDRA (The Indian Journal of Animal Sciences, 2017)
AIREML heritability estimates for production traits F305MY, FTMY and FLL were 0.31±0.09, 0.14±0.06 and 0.04±0.01, respectively. Heritability estimates for binary or threshold traits RP, TUP, LP and PHW were 0.05±0.003, 0.11±0.008, 0.04±0.003 and 0.02±0.001, respectively. Results revealed that disposal was affected to a lesser extent by additive gene action. The estimates of spearman’s rank correlation of production traits with disposal causes were negative. The disposal causes studied under the above analysis can be viewed as indicator of functional performance of dairy cattle. Selection of sires based on superior production performance of its daughters was going to have a negative impact on the functional traits; which underlines the fact that sire evaluation should be inclusive of functional performance of the daughters in addition to the production performance. Such selection would lead to lesser veterinary costs and also reduce the cost of other inputs thus maximizing profits in dairying.